2009
DOI: 10.1177/0266242609338756
|View full text |Cite
|
Sign up to set email alerts
|

Is there Ethnic Discrimination in the UK Market for Small Business Credit?

Abstract: A large-scale survey of UK small business finances is analysed for evidence of ethnic discrimination in the credit market. A summary analysis of credit outcomes (loan denials , loan interest rates and discouragement) reveals large differences across ethnic groups with Black and Bangladeshi businesses, in particular, experiencing poorer outcomes than White and Indian businesses. Econometric analysis indicates that ethnic differencs in denial rates and interest rates can be explained by variations in non-ethnic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
100
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(105 citation statements)
references
References 27 publications
3
100
1
1
Order By: Relevance
“…The results also support other work which, controlling for selection, finds little evidence for ethnic discriminations (Fraser, 2009b).…”
Section: Insert Table 3 Around Heresupporting
confidence: 88%
See 2 more Smart Citations
“…The results also support other work which, controlling for selection, finds little evidence for ethnic discriminations (Fraser, 2009b).…”
Section: Insert Table 3 Around Heresupporting
confidence: 88%
“…To control for this, we estimate a series of probit regression models for whether firms have difficulty obtaining finance (see Fraser et al 2009b;Mina et al 2013;Lee and Drever, 2014 for similar applications). These take two forms: (1) probit regressions where the dependent variable is either application for finance or one of the measures access to finance discussed above, or the choice to apply, and (2) Heckman regressions which also consider success of application for finance but which also control for selection effects in the likelihood of firms to apply for finance.…”
Section: Empirical Strategymentioning
confidence: 99%
See 1 more Smart Citation
“…Cavalluzzo et al (2002) included gender, but did not find a significant influence on loan rates. For small business loans in the U.K., Fraser (2009) found that ethnicity and gender did not influence financial rejection rates and loan rates. None of these studies included age of the entrepreneur as explanatory variable of loan rates or credit availability.…”
Section: Literature Review and Hypothesesmentioning
confidence: 93%
“…This may mean that educational qualifications will have less effect when not combined with practical experience (Fraser, 2009). Consistent with this, Beckers and Blumberg (2013) find second generation immigrants in the Netherlands whilst being more highly educated and socially integrated fail to display improved business performance than first generation immigrants.…”
Section: Challenges Faced By Ethnic Entrepreneurs -Regulations and Mamentioning
confidence: 99%